Unpacking organizational capacity in the context of the Water Framework Directive. Issue 3 (2nd July 2016) - Xerri, Francesca; Jeffrey, Paul; Smith, Heather M.
ABSTRACT: Effective implementation of the European Water Framework Directive (WFD) is dependent on Member States' national water institutions and organizations, often designated as 'competent authorities'. Although substantial research relating to the Directive itself has been carried out, less is known about the extent to which competent authorities have the organizational capacity to deliver it. The literature notes that conceptual understanding of capacity has been hampered by lack of definitional clarity making both its management and assessment challenging. From a combination of extensive literature review, empirical data collection and thematic analysis, we develop an in-depth holistic conceptual framework for the assessment of competent authorities' organizational capacity in the context of WFD delivery. The core thematic components of this framework encourage analysts to consider the ways in which legal authority, information and knowledge, skills, resources and leadership shape a competent authority's ability to deliver WFD objectives. Malta is the case study used to test the application of this method. Focus is drawn on the implementation of three main WFD provisions: Articles 8, 9 and 14. The proposed conceptual framework for unpacking organizational capacity provides insights that are helpful to policy-makers for the future planning of WFD delivery as it highlights the challenges experienced by competent authorities as well as opportunities to invest in and enhance their capacity.